2018
DOI: 10.1371/journal.pone.0193488
|View full text |Cite
|
Sign up to set email alerts
|

Regional inequalities in premature mortality in Great Britain

Abstract: Premature mortality exhibits strong spatial patterns in Great Britain. Local authorities that are located further North and West, that are more distant from its political centre London and that are more urban tend to have a higher premature mortality rate. Premature mortality also tends to cluster among geographically contiguous and proximate local authorities. We develop a novel analytical research design that relies on spatial pattern recognition to demonstrate that an empirical model that contains only soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 29 publications
2
20
0
1
Order By: Relevance
“…Further, the National Research Council and the Institute of Medicine reported that income, education, occupation, sex, and race/ethnicity were vital social factors that are directly connected to chronic diseases [29]. Moreover, previous studies with British men and women (civil government employees) found that those with the highest professional rank had the lowest percentage of deaths (regardless of the cause) [9,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the National Research Council and the Institute of Medicine reported that income, education, occupation, sex, and race/ethnicity were vital social factors that are directly connected to chronic diseases [29]. Moreover, previous studies with British men and women (civil government employees) found that those with the highest professional rank had the lowest percentage of deaths (regardless of the cause) [9,30].…”
Section: Discussionmentioning
confidence: 99%
“…For example, smoking is associated with more than 21 chronic conditions [ 8 ]. Other social determinants such as income, education, occupational characteristics, and racial inequality have direct effects on unhealthy and healthy lifestyles and connections to chronic diseases [ 3 , 9 , 10 ]. Several earlier studies among the various population have revealed that the association between social determinants and chronic diseases [ 11 ], especially cardiovascular diseases [ 12 14 ] and diabetes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, spatial analysis constitutes a valuable approach to reveal geographic patterns of health inequalities and guide local public health policies [19,20]. However, most of the studies assessing mortality variations in a geographic setting are limited to large spatial scales [21][22][23][24], and only a few studies -none in Switzerland-use spatial analysis methods to evaluate small areas inequalities in health. These studies highlighted the association between the geographic disparities of premature death and deprivation status [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Neighbourhood changes involve increasing deprivation, for example, in post-industrial, urban communities. Socio-economic inequalities across British neighbourhoods are considerable and reflected in an almost three times higher risk of premature mortality in deprived than affluent areas, particularly old industrial and urban areas (Plumper et al ., 2018). Rural neighbourhoods are also being transformed.…”
Section: Introductionmentioning
confidence: 99%